Some Aspects Concerning the Designing of Ultrawideband and Pulse Antennas - Titov, A.N. (Радиофизика и радиоастрономия, 2002)
The principally attainable antenna characteristics are discussed, including the ultrawideband antennas. Antenna configuration is pointed out as a principle factor for the antenna characteristics to approach the potentially attainable ones. Both the similarities and the distinctions are considered as regards the approaches to the ultrawideband and the pulse antenna designing. General recommendations are expounded as to the choice of the antenna type and structure for the transmission and reception of pulse electromagnetic signals. Рассматриваются потенциально достижимые характеристики антенн, в том числе сверхширокополосных. Подчеркивается принципиальное влияние конфигурации антенн на степень приближения характеристик антенны к потенциально достижимым. Обсуждается сходство и различие в подходах к проектированию сверхширокополосных и импульсных антенн. Излагаются общие рекомендации, связанные с выбором типов и конструкций антенн, предназначенных для излучения и приема импульсных электромагнитных сигналов. Розглянуто потенційно досяжні характеристики антен, у тому числі надширокосмугових. Підкреслено принциповий вплив конфігурації антен на ступінь наближення характеристик антени до потенційно досяжних. Обговорюється схожість та відмінність у підходах до проектування надширокосмугових та імпульсних антен. Викладено загальні рекомендації, пов’язані з вибором типів і конструкцій антен, призначених для випромінювання і прийому імпульсних електромагнітних сигналів.